EFFECTIVENESS OF MURROTAL AL-QUR'AN THERAPY TO REDUCE ANXIETY IN PRE-OPERATIVE PATIENTS: LITERATURE REVIEW - Ariful Haq; Vita Purnamasari; Endah Tri Wulandari (Keperawatan Anestesiologi Program Sarjana Terapan, 2025)
Background: Surgery is a medical procedure that can cause physical and psychological stress, especially anxiety in the preoperative stage. This anxiety can have a negative impact on the patient's health condition. To overcome anxiety, pharmacological (drug) and non-pharmacological therapy can be used, one of which is murottal Al-Qur'an therapy. This study aims to examine the effect of murottal therapy on patient anxiety levels before surgery through a literature review. Methods: This study uses a literature review method by collecting and analyzing relevant research results regarding the effect of Al-Qur'an murottal therapy on pre-operative patient anxiety. Data were collected from published scientific journals and hospital reports. Results: All articles showed a decrease in anxiety levels after the intervention of Al-Qur'an murottal, both in patients with cataract surgery, fractures, cesarean section, and pre-angiography. The decrease in anxiety was assessed using the HARS and ZSAS scales with statistically significant results (p < 0.05). Conclusion: Al-Quran murottal therapy has been proven effective in reducing pre-operative anxiety in patients and is recommended as a non-pharmacological therapy in the pre-operative care room